An overview of modeling and simulation for lab-on-a-chip applications - Catarino, Susana Oliveira (2013)
The research team has been focused, in the last years, on lab-on-a-chip devices for clinical applications, where the acoustic streaming technique is used for promoting the mixing, the pumping and the chemical reactions of fluids inside the microstructures. This paper describes an overview of the advances achieved by the group in the modeling and simulation areas. In particular, it is focused the modeling and simulation of the acoustic streaming generated by a piezoelectric transducer: poly(vinylidene fluoride) - PVDF. The modeling of the acoustic streaming phenomenon includes the study of the piezoelectric effect generated by the transducers, the compressible NavierStokes equations and the heat transfer equations. The numerical results validate the experimental results previously achieved by the team and may represent a potential breakthrough in microfluids mixing.